Configuring Lecturer Well-Being Policy Deliberation on YouTube: A Critical Study of Virtual Netnography through a Systematic Literature Review - Anam, Choirul; Wardiyanto, Bintoro; Widodo, Suko (The Sunan Ampel Review of Political and Social Sciences, 2025)
This research aims to examine how the YouTube platform is used as a digital public space in articulating social policy discourse, especially related to the welfare of lecturers. Using the Systematic Literature Review (SLR) approach, as many as 22 scientific articles from highly reputable journals were analyzed to identify discourse configurations, representation strategies, and affective, performative, and algorithmic dynamics that shape public opinion related to the issue. The results show that YouTube acts as an alternative deliberative arena that allows academic actors to voice criticism, strengthen the legitimacy of personal experiences, and form digital solidarity. However, not all interactions on these platforms reflect rational deliberation in the Habermasian sense; Many of them are driven by emotional logic and algorithmic selection mechanisms. These dynamics result in complex discourse configurations, where affection and performativity are important elements in building policy narratives. This research contributes to the development of social policy studies and digital public spaces by emphasizing the importance of reading the deliberation process in the context of platform mediation and digital culture. Suggestions for further research include exploration of direct netnography and comparative studies between digital platforms to understand the variations in policy discourse dynamics in more depth.